Determining effects of controllable factors on flawless operations of tanker terminals: Tupras case study - TUNCALI YAMAN, TUTKU (My University, 2022)
Tanker terminals operations’ common aim is to obtain the ships’ flawless operations by minimizing idle time (port-staying time) either in anchorage and/or berthing. In this paper, we accepted the current operating system and structure of Tupraş port in Aliağa İzmir, Turkey as a pre-admitted factor and aimed to understand the determinative effects of the vessel’s length, gross tonnage, and underwater depth on the port-stay time. The data of 99 vessels that visited the port various times in 2021 were collected and modeled over the port-stay time. According to the results, gathered by a generalized linear model with gamma-link function, the average port-stay is approximately 4.9 hours. When the vessel’s overall length or gross tonnage increases by 1 unit, port stay time would increase up to 1 additional hour. Effect of interaction terms on port stay showed the same effect with the vessel’s overall length and the gross tonnage.